Entrepreneurship education courses across multidisciplinary programmes at a South African university of technology: educator and student perspectives - Price, Kariema (Graduate School of Business (GSB), 2019)
Research in the field of entrepreneurship education suggested the need for more studies that focus on the characteristics of the pathways to entrepreneurship education. Previous empirical work in this field has largely been driven by uncovering the link between entrepreneurship education and its impact on students, while fewer researchers have focused on the alignment between the components that constitute entrepreneurship education. The purpose of this mixed methods study was to explore the contextual factors affecting entrepreneurship courses (design and delivery) and their subsequent effects on student perceptions of entrepreneurship and entrepreneurship education across multidisciplinary programmes within a higher education institution. A key aspect of this study was to determine whether students across disciplines were inspired and stimulated by the content and pedagogical aspects of their courses. In this mixed method convergent parallel design study, the qualitative component consisted of semi-structured interviews, presenting the narrative of ten educators teaching in entrepreneurship education. For the quantitative component, survey questionnaires were administered to a sample of 640 students across multidisciplinary programmes at a higher education institution. These surveys were designed to capture the student perceptions of entrepreneurship and entrepreneurship education, as well as their experience of the entrepreneurship course. Key findings of this research identified four factors affecting entrepreneurship education courses within the higher education institution as those of: course design and delivery; institutional impact; educator aspect and the student aspect. Analysis of the student aspect established the influence of contextual factors affecting student perception including: employment aspirations; prior exposure to entrepreneurship education; socio-cultural influence; employment confidence and student experience of the course. This study proposed a conceptual model presenting a framework for teaching in entrepreneurship that highlights the need for an alignment between the factors affecting entrepreneurship education. This conceptual framework therefore provides a map for (a) higher education institutions aiming to implement entrepreneurship education without assimilating its entrepreneurial flavour, (b) curriculum designers of multi-disciplinary programmes and course planners of entrepreneurship education, and (c) educators in entrepreneurship education aiming to develop not only their teaching practice in this field but also enhance their career trajectory in an fast evolving field of education. Firstly, this study contributes to the growing field of research in entrepreneurship education as it is offered within the higher education system, particularly in South Africa where keen efforts are directed at improving and developing this field through current and ongoing initiatives and implementation plans. Secondly, this research also offers an insight into the challenges faced by educators teaching in entrepreneurship, the positioning of entrepreneurship education courses, particularly within multidisciplinary programmes taught at university level and the dynamic of the student input factor. Considering these insights could provide opportunities for improving entrepreneurship education curricula within the higher education institution, not only from a course design perspective but also in the way courses are delivered. Further expectations from this research would be to promote the status of institutionalised entrepreneurship education courses within the higher education community and to acknowledge the written and unwritten role and expectations of educators in this field. This should encourage opportunities for faculty training and development in entrepreneurial learning, benefitting both educator and student.